Chronic kidney disease and inflammatory cytokines in rheumatoid arthritis: a potential pathogenic link - Hironari Hanaoka; Takumi Aoki; Taiji Kosaka; Shoichi Yoshinaga; Akiko Shibata; Ryota Sakai; Takahiko Kurasawa; Koichi Amano (Immunological Medicine)
Recent evidence indicates an increased risk of chronic kidney disease (CKD) in patients with rheumatoid arthritis (RA), with prevalence rates ranging from 20.8% to 24.5%. Risk factors for CKD among RA patients include advancing age, diabetes, cardiovascular disease, hypertension and RA disease activity. Medications such as glucocorticoids and nonsteroidal anti-inflammatory drugs (NSAIDs) may also accelerate CKD progression. Inflammatory cytokines, notably interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and IL-1, play significant roles in the pathogenesis of both RA and CKD, promoting systemic inflammation and renal impairment. Elevated levels of various cytokines have been detected in the plasma and urine of CKD patients, and they raise morbidity and mortality rates, even during early disease stages. Effective management of RA activity and modifications in treatment to reduce renal burden are essential for lowering CKD risk and improving patient outcomes. Biological disease-modifying antirheumatic drugs (DMARDs), particularly those targeting IL-6 and TNF-α, show potential in mitigating CKD progression in RA patients. However, individualized treatment and careful kidney function monitoring are critical, as CKD may impact RA management. Future research should focus on therapeutic strategies that address inflammation in both RA and CKD to optimize patient care.